Kazakhstan’s Anti-China Protests: Implications for the Belt and Road Initiative in Central Asia - Gökçen Gürel Yeşilçimen; Muhammet Koçak (Alternatif Politika)
This article examines China’s increasing investments in Kazakhstan amid its declining soft power and growing public dissent. Focusing on Kazakhstan's strategic position within the Belt and Road Initiative, it analyzes how Chinese economic influence persists despite widespread protests and negative public opinion. Using a qualitative approach, the study synthesizes academic literature, policy analyses, news reports, and firsthand accounts to understand local views on Chinese influence. Findings show that while China’s economic power supports continued investment, the lack of soft power presents long-term risks. Without efforts to improve its image and build trust, China’s reliance on hard power may fuel anti-China sentiments, potentially leading to organized resistance and policy changes in Kazakhstan. The study emphasizes that China must incorporate soft power elements into its foreign policy to sustain influence in Kazakhstan and across Central Asia.